(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article reveals that the development of students’ oral speech is the main goal of language education. In the course of the lesson, it was emphasized that it is necessary to use materials related to the development of speech organically with theoretical topics. The importance of text analysis, working with dictionaries, and especially the use of explanatory dictionaries in the development of students’ speech is shown.